Observability and "second-order acts" - Nabil I. Al-Najjar; Luciano I. De Castro (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2010)
This note questions the behavioral content of second-order acts and their use in decision theoretic models. We show that there can be no verification mechanism to determine what the decision maker receives under a second-order act. This impossibility applies even in idealized repeated experiments where infinite data can be observed.
Keywords: 330